Numerical simulations in astrophysics:Supernovae explosions, magnetorotational model and neutrino emission - G. S. Bisnovatyi-Kogan (Discrete Dynamics in Nature and Society)
Theories of stellar evolution and stellar explosion are based on results of numerical simulations and even qualitative results are not available to get analytically. Supernovae are the last stage in the evolution of massive stars, following the onset of instability, collapse and formation of a neutron star. Formation of a neutron star is accompanied by a huge amount of energy, approximately 20% of the rest mass energy of the star, but almost all this energy is released in the form of weakly interacting and hardly registrated neutrino. About 0.1% of the released neutrino energy would be enough for producing a supernovae explosion, but even transformation of such a small part of the neutrino energy into the kinetic energy of matter meets serious problems. Two variants are investigated for obtaining explosion. The first one is based on development of convective instability, and more effective heating of the outer layers by a neutrino flux.